PENGGUNAAN LAYANAN BIMBINGAN KLASIKAL GUNA MENINGKATKAN LITERASI KEBENCANAAN BAGI SISWA [USING CLASSICAL GUIDANCE SERVICES TO IMPROVE DISASTER LITERACY FOR STUDENTS] - Rahmat, Hayatul Khairul (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2023)
This research aims to examine the use of classical guidance services to increase disaster literacy among students. This research uses qualitative research methods with a literature study approach. The findings from this research are that classical guidance services are a preventive strategy carried out by a guidance and counseling teacher to help students face problems that arise in the future and also prepare students to face things. In this case, in order to increase disaster literacy, classical guidance services can equip students to know information about disasters and have awareness of potential disasters that will occur so that they can prepare themselves and know how to deal with disasters.